Single-molecule localization microscopy allows for the analysis of cancer metastasis-specific miRNA distribution on the nanoscale - Aliaksiuk, Volha; Abba, Mohammed L.; Patil, Nitin; Hafner, Mathias; Altevogt, Peter; Cremer, Christoph; Allgayer, Heike (OncoTarget, 2015)
Oncotarget | https://doi.org/10.18632/oncotarget.6297 Olga Oleksiuk, Mohammed Abba, Kerem Can Tezcan, Wladimir Schaufler, Felix Bestvater, Nitin Patil, Udo Birk, Mathias Hafner, Peter Altevogt, Christoph Cremer,...
Gesehen am 18.10.2017